Coronary Microvascular Dysfunction in Patients With Systemic Lupus Erythematosus and Chest Pain - Manchanda, Ashley S.; Kwan, Alan C.; Ishimori, Mariko; Thomson, Louise E. J.; Li, Debiao; Berman, Daniel S.; Bairey Merz, C. Noel; Jefferies, Caroline; Wei, Janet (Frontiers in Cardiovascular Medicine, 2022)
Chest pain is a common symptom in patients with systemic lupus erythematosus, an autoimmune disease that is associated with increased cardiovascular morbidity and mortality. While chest pain mechanisms can be multifactorial and often attributed to noncoronary or noncardiac cardiac etiologies, emerging evidence suggests that ischemia with no obstructive coronary arteries (INOCA) is a prevalent condition in patients with chest pain and no obstructive coronary artery disease. Coronary microvascular dysfunction is reported in approximately half of SLE patients with suspected INOCA. In this mini review, we highlight the cardiovascular risk assessment, mechanisms of INOCA, and diagnostic approach for patients with SLE and suspected CMD.